The Future of Indo-China Military Rivalry - Mr. Muhammad Sarmad Zia; Ms. Maryam Zubair (CISS Insight Journal, 2017)
The June-August border crisis between the People’s Republic of China and India at the Doklam Plateau stirred the political and security environment of the region. What started off as a Chinese road project in Doklam, a disputed territory between Bhutan and China, soon took the shape of border troops’ engagement between Indian and China. India claims that it acted on behalf of Bhutan.1 A treaty signed between India and Bhutan in 1949, known as the Treaty of Friendship empowered India to control both foreign and defence policies of Bhutan and act on its behalf.2 The issue’s origin lies in Bhutan laying claim to the Doka La Plateau, however the claim is refuted by China on the basis that historically the territory was a part of Tibet. The issue has subsided for now, but at the peak of the conflict, both China and India were persistent that the other should withdraw their forces. The crisis was averted as both sides agreed to resolve the issue amicably. While India and China have multiple disputed borders, like Aksai Chin and Aruanchal Pradesh, the focus of this paper will be on the one at the tri-junction of India, China and Bhutan. This paper will discuss how an issue such as the standoff at Doklam in addition to other border issues, in tandem with military modernization, naval competition, nuclear signaling, and US involvement in the region may lead to a larger scale conflict, or war, between the two nuclear powers.